Poor oral hygiene as trigger of diabetes mellitus progressiveness - Sunarko Setyawan (Dental Journal (Majalah Kedokteran Gigi), 2006)
Diabetes mellitus is a systemic disease with several major complications affecting both the quality and length of life. The disease is characterized by increasing susceptibility to infection that important risk factor for oral infection progressiveness; periodontitis, infection or lesions. Infection progressiveness and inflammation can increase blood cytokines. The cytokines modulate cells up and down regulation moreover apoptosis or necrosis cells. The increasing of the blood cytokines that implicate in the process of pancreatic β-cell destruction is not fully understood. Poor oral hygiene stimulate proinflammatory cytokines (such as: IL-1, IL6, TNF-alpha, etc.) and make chronic infection worse. IL-1β and/or TNF-α plus IFN-γ induce β-cell apoptosis via the activation of β-cell gene networks under transcription controlling factors, such as NF-κβ (nuclear factor-κβ) and STAT-1 (signal transducers and activators of transcription-1). Others mechanism of the decreased β-cell function may activate cytokines stimulated macrophages. The presence of activated macrophages within pancreatic islets in insulin-dependent diabetes mellitus suggests an involvement of ß-cell death. This paper describes that poor oral hygiene are high predisposition on the diabetic progressiveness.